2020
DOI: 10.3389/fcvm.2020.602183
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MSC Therapy in Attenuating the Damaging Effects of the Cytokine Storm Induced by COVID-19 on the Heart and Cardiovascular System

Abstract: The global pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 2019 (COVID-19) has led to 47 m infected cases and 1. 2 m (2.6%) deaths. A hallmark of more severe cases of SARS-CoV-2 in patients with acute respiratory distress syndrome (ARDS) appears to be a virally-induced over-activation or unregulated response of the immune system, termed a “cytokine storm,” featuring elevated levels of pro-inflammatory cytokines such as IL-2, IL-6, IL-7, IL-22, CXCL10, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 282 publications
(373 reference statements)
0
22
0
Order By: Relevance
“…We checked whether this list of 75 host proteins was significantly enriched in genes annotated to pathways, using the ClueGO application [ 16 ] ( Figure 1 A) and identified an enrichment of genes that are involved in mitochondrial transport, tRNA processing, and maturation of proteins (e.g., RAB geranylgeranylation and N-Glycan biosynthesis) ( Table S2 ). Although mitochondrial dysfunctions have been linked to SARS-CoV-2 pathogenesis [ 17 , 18 , 19 , 20 ], no additional link between proteins enriched in the list and cell functions perturbed by viral infection was revealed by this classical GSEA approach. This could be explained by noting that many proteins in the list of the 75 SARS-Cov-2 binders are not annotated to pathways ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We checked whether this list of 75 host proteins was significantly enriched in genes annotated to pathways, using the ClueGO application [ 16 ] ( Figure 1 A) and identified an enrichment of genes that are involved in mitochondrial transport, tRNA processing, and maturation of proteins (e.g., RAB geranylgeranylation and N-Glycan biosynthesis) ( Table S2 ). Although mitochondrial dysfunctions have been linked to SARS-CoV-2 pathogenesis [ 17 , 18 , 19 , 20 ], no additional link between proteins enriched in the list and cell functions perturbed by viral infection was revealed by this classical GSEA approach. This could be explained by noting that many proteins in the list of the 75 SARS-Cov-2 binders are not annotated to pathways ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cytokine storm can result in MODS in COVID-19 patients with a worse prognosis. Myocarditis, pericarditis, decompensated heart failure, cardiogenic shock, edema, myocardial fibrosis as some cardiovascular complications ( Ellison-Hughes et al, 2020 ; Vitiello and Ferrara, 2020 ); respiratory distress symptoms including dyspnea and tachypnea and decreased arterial oxygen saturation ( Parhizkar Roudsari et al, 2020 ); renal damage symptoms such as AKI, hyperkalemia, higher levels of uric acid, BUN, D-dimer, and creatinine as well as hematuria and proteinuria ( Kunutsor and Laukkanen, 2020 ; Patel et al, 2020 ; Puelles et al, 2020 ); an abnormal ALT or AST levels along with slightly increased bilirubin and low albumin (for liver damage consequences) ( Sun J. et al, 2020 ; Wu J. et al, 2020 ); and headache, malaise, unstable walking as well as cerebral hemorrhage and cerebral infarction, meningitis/encephalitis, stroke, anosmia, and ageusia as some nervous system damages ( Alomari et al, 2020 ; Berger, 2020 ) can be mentioned as some of the important organ involvements of COVID-19 due to cytokine storm. GF, growth factor; IL, interleukin; TNF, tumor necrosis factor; IFN, interferon; CSF, colony-stimulating factor; MODS, multiple-organ dysfunction syndrome; TGF-β, transforming growth factor beta; AKI, acute kidney injury; BUN, blood urea nitrogen; ALT, alanine aminotransferase; AST, aspartate aminotransferase.…”
Section: Cytokine Stormmentioning
confidence: 99%
“…Cytokine storm along with other mechanisms including thrombosis, endotheliosis, and lymphocytopenia can cause this cardiac damage or make it worsen ( Unudurthi et al, 2020 ). Thus, the cardiovascular system can be involved in virus extrapulmonary effects with diverse manifestations of myocarditis, pericarditis, decompensated heart failure, cardiogenic shock, edema, myocardial fibrosis, and some other complications ( Ellison-Hughes et al, 2020 ; Vitiello and Ferrara, 2020 ). The virus can cause its effects on the cardiac system through different ways of direct infection, binding to the functional receptors of ACE2, and immune damage.…”
Section: Cytokine Stormmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that bone marrow mesenchymal stromal cells (MSCs) could accelerate the cardiac function recovery of MI animals by decreasing fibrosis and infarct area [ 5 , 6 ]. Meanwhile, MSCs could inhibit the damaging effects of the cytokine storm induced by COVID-19 on the heart and cardiovascular system [ 7 ]. MSCs have been widely used in many fields [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%